2014
DOI: 10.1186/1748-717x-9-165
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for breast cancer acceleration of the START A treatment regime: intermediate tolerance and efficacy

Abstract: PurposeProspective evaluation of accelerated hypofractionated radiotherapy (RT) in breast cancer patients treated with 41.6 Gy in 13 fractions plus boost delivered five times a week.Patients and methodsBetween 03/2009 and 10/2012 98 consecutive patients aged >55 years presenting with breast cancer (invasive cancer: n = 95, ductal carcinoma in situ (DCIS): n = 3) after breast conserving surgery were treated in our institution with the following schedule: 41.6 Gy in 13 fractions 4 times a week and 9 or 12 Gy boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 18 publications
(27 reference statements)
1
27
0
4
Order By: Relevance
“…Nonetheless, in addition to the phase II prospective trial on our regimen that we have reported earlier, the data are constantly being accumulated. 10 The interim efficacy of 41.6 Gy in 13 fractions and then sequential boost with the same regime as ours reported by Janssen et al 20 was a local control rate of 100% at 2 years.…”
Section: Discussionmentioning
confidence: 53%
“…Nonetheless, in addition to the phase II prospective trial on our regimen that we have reported earlier, the data are constantly being accumulated. 10 The interim efficacy of 41.6 Gy in 13 fractions and then sequential boost with the same regime as ours reported by Janssen et al 20 was a local control rate of 100% at 2 years.…”
Section: Discussionmentioning
confidence: 53%
“…Après irradiation totale du sein, certaines études évaluent l'ajout de la surimpression avec l'hypofractionnement [15]. Le boost semble réa-lisable sans réaction cutanée inacceptable [10,11]. L'intérêt de ces études ne sera réel que si elles passent dans la pratique quotidienne.…”
Section: Discussionunclassified
“…Pour ces raisons, le schéma en 15 séances a pu être préféré à ceux en 13 séances. Enfin, des études récentes ont montré la possibilité d'un boost tumoral, avec des résultats cosmétiques acceptables, permettant de considérer une extension des indications de l'hypofractionnement [10,11].…”
Section: Introductionunclassified
“…We measured physical ability using the HGS. At the time of anthropometric measurement, after completing all measurements above, the participants were asked to grab a hand dynamometer with the arm position perpendicular to the axial [20][21] . Next, handgrip strength was measured twice with 2 minutes interval using a hand dynamometer.…”
Section: Biochemical Analysis Physical Measurements Patient-generated -Subjective Global Assessment (Pg-sga) and Quality Of Life (Qol)mentioning
confidence: 99%